THE USE OF GROUP FORMS OF TRAINING AT PATHOPHYSIOLOGY CLASSES WITH FOREIGN STUDENTS - Hryshko, Yu.M. (World of Medicine and Biology, 2017)
The task of teaching staff in higher education today, based on the targets set, is to select from their methodical achievements all progressive means and thus to change, modernize the educational process, ensuring its research and exploratory character [1, 4, 10]. This approach will contribute to establishing a creative atmosphere in the group of foreign students, development of thinking, and abilities. This should be non-violent learning, but encouragement for cognition, respect for the intellectual strength of the student. Freedom and right to choose will determine not only the best results in learning, but also contribute to their formation as individuals, which will be an impetus for independent cognitive activity, the ability to set and solve new problems [5].It should be emphasized that one of the directions for increasing the efficiency of the educational process in pathophysiology is the use of group forms of training.
Keywords: pathophysiology; foreign students; group forms of training